Evaluating the long-term benefits of hydroxyurea in pediatric sickle cell anemia - Paul George; Grace Kalmus; Peter A. Lane; Wilbur Lam; Joseph Lipscomb; David Howard (Blood Advances)
Abstract: Hydroxyurea is the primary disease-modifying medication for sickle cell anemia (SCA), but its long-term effects, particularly how these effects change over time, are not well understood. This study aimed to quantify the effects of hydroxyurea on clinical and laboratory outcomes in children with SCA over a prolonged period of use. We conducted a quasi-experimental study using contemporary difference-in-differences and dynamic event study analyses on a longitudinal cohort of 2147 children with SCA (hemoglobin SS or hemoglobin SSβ0, HbSS/HbSβ0) from 2010 to 2021. The primary outcomes included emergency department (ED) visits per year, hospital days per year, and annual average hemoglobin concentration. Hydroxyurea use was associated with fewer ED visits per year (average treatment effect on the treated [ATT], −0.36 visit per year; 95% confidence interval [CI], −0.57 to −0.16) and fewer hospital days per year (ATT, −0.84 d/y; 95% CI, −1.51 to −0.17) with sustained effects over time. On average, the hemoglobin concentration increased with hydroxyurea use (ATT, 0.56 g/dL; 95% CI, 0.39-0.73), but the sustained effect was observed only among the subgroup with laboratory markers of good adherence. This study demonstrates that hydroxyurea has sustained clinical benefits in reducing ED visits and hospital days across years of use in children with SCA. These findings provide perspective for clinicians and families regarding the long-term efficacy of hydroxyurea in pediatric SCA management and underscore the importance of ongoing adherence counseling to optimize clinical benefit. Furthermore, this study design provides a methodological framework for rigorously and causally evaluating other SCA-specific treatments, such as stem cell transplant and gene therapy, in real-world settings.